Synthetic Earthquake Accelerogram of Kupang City Based on SNI 8899:2020 - Niakku Imanuel Maggang (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2026)
In order to make it a sustainable and safe city as a settlement, Kupang City requires the availability of earthquake-resistant buildings because its location on Timor Island is in an earthquake-prone area. In designing earthquake-resistant buildings, there is a method, namely the time history analysis method, which better shows the actual conditions at the time of the earthquake because it includes earthquake load parameters in the time function (dynamic load). This method requires an earthquake accelerogram as an earthquake load in the analysis process. Not all areas have earthquake accelerogram recordings, so it is necessary to create a synthetic earthquake accelerogram as a substitute for the earthquake accelerogram at the location where a building will be planned. In this paper, eleven pairs of synthetic accelerograms were created for the Kupang City location for the medium soil site class (SD) by referring to SNI 8899:2020 and the Indonesian Earthquake Hazard Deaggregation Map for Earthquake Resistant Infrastructure Planning and Evaluation which is a derivative of SNI 1726:2019. The creation of synthetic earthquake accelerograms in this paper uses the Amplitude Scaling Method using a period range of 0.2 seconds - 2 seconds for three earthquake source mechanisms, namely the Benioff earthquake source, the Shallow Fault earthquake source, and the Megathrust earthquake source. From each earthquake source, eleven pairs of horizontal earthquake accelerograms were taken that met the location criteria and then selected based on the significant duration of each pair of accelerograms. The results of the study are eleven pairs of synthetic earthquake accelerograms for the Kupang City location which can be used as dynamic earthquake loads in time history analysis. The eleven synthetic accelerograms are modifications of the original earthquake accelerograms on the earthquake accelerogram database website with the following Regional Seismic Network (RSN) numbers: RSN 9, RSN 36, RSN 51, RSN 4007390, RSN 4017018, RSN 4017032, RSN 4017055, RSN 4032461, RSN 4028440, RSN 4028606, and RSN 4032589.